Thermal design and characterization of a modular integrated liquid cooled 1200 V-35 A SiC MOSFET bi-directional switch. (September 2017) - Cova, P.; Aliyu, A.M.; Castellazzi, A.; Chiozzi, D.; Delmonte, N.; Lasserre, P.; Pignoloni, N.
Abstract: The aim of this work is the thermal design of a modular direct liquid cooled package for 1200 V–35 A SiC power MOSFETs, in order to take full advantage of the high power density and high frequency performance of these devices, in the development of a modular integrated solution for power converters. An accurate electro-thermal fluid dynamic model is set up and validated by thermal characterization on a prototype; numerical models have been used to study the internal temperature distribution and to propose further optimization.